Biomarker identification for rheumatoid arthritis with inadequate response to DMARD and TNF therapies using multidimensional analyses - Leyuan Li; Hui Guo; Weijin Zhang; Xi Xiang; Jun Chi; Mengmeng Zhang; Jiali Chen; Zhimin Wang; Liping Dai (Immunobiology)
Purpose: Rheumatoid arthritis (RA) is an immune system disorder disease accompanied with severe joint damage. However, the molecular mechanism of RA with insensitive to medicine remains insufficient. Thus, this study aims to identify the biomarkers of RA patients with inadequate responses (IR) toward disease-modifying antirheumatic drug (DMARD) and antitumor necrosis factor (TNF) therapies, using multidimensional analyses. Methods: Gene expression data GSE45291 originating from clinics were downloaded from the Gene Expression Omnibus public database (GEO). Differentially expressed genes (DEGs) closely associated with DMARD&TNF-IR RA were identified using the Limma R package. Weighted gene co-expression network analysis (WGCNA) was carried out to identify critical genes. The CIBERSORT algorithm and single sample Gene Set Enrichment Analysis (ssGSEA) were employed for immune infiltration analysis and functional enrichment analysis, respectively. Lastly, mRNA expression levels of the identified hub genes in inflammatory conditions of collagen-induced arthritis (CIA) rats and lipopolysaccharide (LPS)-induced RAW264.7 cells were further observed using RT-qPCR. Results: In this work, a total of 17 genes were identified as hub genes. Of these, the expression levels of UHMK1, ELK4, APOC2, and SFT2D1 were significantly lowered in inflammatory conditions. GSEA indicated B cells with the immune-related genes play an essential role in the course of DMARD&TNF-IR RA. Notable differences in immune cell proportions (activated. Dendritic. cell, CD56 bright. Natural. killer. Cell, gamma. Delta. T. cell, MDSC, macrophage) were observed between normal and disease groups, suggesting immune involvement. Conclusion: The findings of this study provide additional understanding of the detection of DMARD&TNF-IR RA.